RETRACTED: Raza et al. Mechanical, Durability, and Microstructural Evaluation of Coal Ash Incorporated Recycled Aggregate Concrete: An Application of Waste Effluents for Sustainable Construction. Buildings 2022, 12, 1715 - Ali Raza; Noha Saad; Khaled Mohamed Elhadi; Marc Azab; Ahmed Farouk Deifalla; Ahmed Babeker Elhag; Khawar Ali (Buildings, 2025)
The journal retracts the article titled “Mechanical, Durability, and Microstructural Evaluation of Coal Ash Incorporated Recycled Aggregate Concrete: An Application of Waste Effluents for Sustainable Construction” [...]